Epistemologi Tauhidik-Integratif sebagai Kritik terhadap Sains Modern: Analisis Pemikiran Syed Muhammad Naquib al-Attas dan Seyyed Hossein Nasr - Yuldelasharmi Yuldelasharmi; Syukri Iska; Yulfian Yulfian; Jamaluddin Jamaluddin; Septika Rudiamon (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2025)
This article examines the Islamization of science as an epistemological response to the crisis of modern science characterized by the secularization of knowledge, fragmentation of disciplines, and the separation between facts, values, and transcendental meaning. The analysis focuses on the thought of Syed Muhammad Naquib al-Attas and Seyyed Hossein Nasr as two leading Muslim intellectuals who offer fundamental critiques of the modern scientific paradigm from the perspective of Islamic epistemology. Rather than merely comparing their ideas, this study aims to formulate a conceptual synthesis that advances the theoretical discourse on the Islamization of science. Employing a qualitative approach with an epistemological–comparative analysis of the primary works of al-Attas and Nasr, the study is complemented by literature from the philosophy of science and contemporary debates on the crisis of knowledge. The findings reveal that al-Attas emphasizes the purification of the concept of knowledge and the formation of an Islamic worldview grounded in adab, while Nasr underscores the necessity of resacralizing science through metaphysical and cosmological awareness. Based on these analyses, the article proposes a tauhidic–integrative epistemology as its main theoretical contribution, positioning tawḥīd as the unifying principle of revelation, reason, and empirical experience in the development of knowledge. This study argues that the Islamization of science should be understood as a constructive epistemological project with continued relevance for global discussions on science, ethics, and civilizational sustainability.